An efficient method for rendering linear symbols on 3D terrain using a shader language. Issue 3 (4th March 2018) - She, Jiangfeng; Li, Chuang; Li, Jiaqi; Wei, Qiujun
ABSTRACT: With the extensive application of virtual geographic environments and the rapid development of 3D visualization analysis, the rendering of complex vector lines has attracted significant attention. Although there are many rendering algorithms in 3D geographic information system (GIS), they are not sufficiently flexible to meet the requirements for rendering linear symbols composed of diverse colors and shapes. However, the interactive rendering of a scene and the accuracy of the symbols are important components for large-scale, complex vector lines. In this paper, we propose a graphics processing unit (GPU)-accelerated algorithm for rendering linear symbols on 3D terrain. Symbol rendering is embedded within the terrain-rendering process, and vector lines are encoded in a 3D texture and then transferred to the GPU. A set of visual properties are used to enrich the expression of symbols with the help of geometric operations in the fragment shader. A series of experiments demonstrate that the proposed method can be utilized for drawing various pixel-exact linear symbols and can achieve real-time rendering efficiency.